2019
DOI: 10.1021/acs.jpcc.9b06500
|View full text |Cite
|
Sign up to set email alerts
|

On the Reactivity of the Cu/ZrO2 System for the Hydrogenation of CO2 to Methanol: A Density Functional Theory Study

Abstract: Zirconia-modified copper catalysts are being actively discussed to be beneficial in CO2/H2 conversion to methanol. The nature of the promotional effect of ZrO2 is still an intense matter of debate. Here, we report a density functional theory study investigating the CO2 hydrogenation reaction using a tetragonal ZrO2(101)-supported copper nanowire model of the copper–zirconia interface. We calculated adsorption energies of reactants and intermediates relevant for CO2 hydrogenation at different copper and zirconi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(70 citation statements)
references
References 61 publications
4
65
0
Order By: Relevance
“…The exact cause of the promotional effect of ZrO 2 is still vividly debated [14,15,17,[21][22][23]. Among the possibilities being discussed are an enhanced CO 2 adsorption by ZrO 2 [11], and an increased adsorption at the Cu-ZrO 2 interface [14,24] or at copper particles in close contact with the ZrO 2 support [25].…”
Section: Introductionmentioning
confidence: 99%
“…The exact cause of the promotional effect of ZrO 2 is still vividly debated [14,15,17,[21][22][23]. Among the possibilities being discussed are an enhanced CO 2 adsorption by ZrO 2 [11], and an increased adsorption at the Cu-ZrO 2 interface [14,24] or at copper particles in close contact with the ZrO 2 support [25].…”
Section: Introductionmentioning
confidence: 99%
“…On this so positively charged Cu, which just for the sake of clarity must be in the form of very small nanoparticles or even clusters, the barrier of H 2 O dissociation is small, and the WGS reaction is enhanced [84]. Recently, Polierer et al [85] have found that the interphase, although critical, is not the adsorption site of the reactants and intermediates during the CO 2 hydrogenation. They have reported a volcano-shaped relation between the activity and the adsorption energy of various sites of a modelled Cu/ZrO 2 system ( Figure 5).…”
Section: Copper-zirconia Catalysts For the Methanol Economymentioning
confidence: 99%
“…For instance, Azenha et al [94] have described a quite active CuPd catalyst on m-ZrO2 active at 180 °C ( Figure 6). Alternatively, CeO2 is introduced However, there is still debate on which is the precise role of each site and on which reaction pathway is the most favorable [52,60,[85][86][87]. Formate (HCOO) has been recognized in many studies as an intermediate during MS [88] and MSR alike (see below).…”
Section: Copper-zirconia Catalysts For the Methanol Economymentioning
confidence: 99%
See 1 more Smart Citation
“…Both direct and indirect promotion of Cu by ZrO 2 has been suggested based on theoretical and experimental investigations. Polierer et al (2019) studied the Cu/ZrO 2 interface by density functional theory (DFT) calculations. Their results indicate that the intermediates bind too strongly on the ZrO 2 surface as well as on the Cu/ZrO 2 interface for further hydrogenation to methanol.…”
Section: Effect Of Other Metal Oxide Components On Cu-based Catalystsmentioning
confidence: 99%